Learning Entity framework core - Loukas, Dimitris (Packt, 2017)
"Entity Framework is a highly recommended Object Relation Mapping tool used to build complex systems. This course provides a full learning path to getting productive with the Entity Framework Core. Designed with the intermediate developer in mind and utilizing all of the latest features introduced by EF Core 2.0 and ASP.NET Core 2.0. In this course, you will learn how to create, execute and rollback your own migrations. You will also get familiar with everything you need to create complex relational models. You will explore some of the most important advanced features of the entity framework like shadow properties, database generated values and raw SQL queries. You will know how to take an existing database and write a project based upon it with minimal intervention."--Resource description page